TINGKAT KESEHATAN HUTAN MANGROVE DALAM HUBUNGANNYA DENGAN PERUBAHAN IKLIM (Studi Kasus Mangrove Pesisir Timur Kabupaten Lampung Timur) - Rahmat Safe’i (Jurnal Hutan Tropis, 2021)
The condition of mangrove forests on the east coast of East Lampung Regency is currently experiencing degradation and has suffered a lot of damage due to various causes and problems it faces. This condition causes the role and benefits and functions of mangrove forests to decrease, especially in climate change. Therefore, to determine the condition of the mangrove forest, periodic monitoring and assessment of mangrove forest health is required. The purpose of this study was to determine the importance of mangrove forest health in climate change. To achieve this, the stages include: determining the number of plot clusters to be made, making cluster plots, measuring the health of mangrove forests based on ecological indicators of mangrove forest health, processing and analyzing mangrove forest health data using SIPUT (Assessment Information System) software. Forest Health), and categorization and health assessment of mangrove forests. The results of this study indicate that the condition of mangrove forests on the East coast of East Lampung Regency in general has a forest health condition in the medium category. So, knowing the health condition of mangrove forests will affect climate change. Forest health makes mangrove plants grow with good physiological processes so that they can absorb carbon dioxide in the atmosphere optimally. These conditions will make the environment better.